Intervensi cookies ikan gabus apel (Igapel) terhadap asupan makronutrien dan kadar glukosa darah pada pasien diabetes mellitus tipe 2 - Hanan Hanan; Annasari Mustafa; Fifi Luthfiyah; Etik Sulistyowati (Jurnal Gizi Klinik Indonesia, 2026)
Igapel snakehead fish and apple cookies intervention on macronutrient intake and blood glucose levels in type 2 diabetes mellitus patientsBackground: Type 2 diabetes mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion or insulin resistance. Nutritional innovations, such as cookies made from snakehead fish and Rome Beauty apples, may support nutritional management in patients with DM. The protein content in snakehead fish is known to inhibit the α-glucosidase enzyme, while apple fiber slows the rate of blood glucose absorption. Objective: This study aimed to analyze the effects of snakehead fish and apple cookies on energy, macronutrient, and fiber intake, as well as random blood glucose levels, in patients with type 2 DM at Dr. Sayidiman Hospital, Magetan, East Java Province, Indonesia.Methods: The study used a quantitative approach with a quasi-experimental design and a pre-posttest control-group model. A total of 32 respondents were selected through purposive sampling techniques and divided into intervention groups and control groups. Cookies were given twice a day for three days. Data were analyzed using JASP software.Results: The paired t-test showed significant increases in energy and macronutrient intake, and in fiber intake (p < 0.001), as well as a significant decrease in random blood glucose levels (p < 0.001). Meanwhile, the results of the independent t-test indicated a significant difference in post-intervention random blood sugar levels between groups (p=0.002).Conclusions:  Snakehead fish and apple cookies significantly increase nutrient intake while helping to control random blood glucose levels in patients with type 2 DM.